2010
DOI: 10.1002/pros.21259
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors are differentially expressed in Gleason patterns of prostate cancer and down‐regulated in matched lymph node metastases

Abstract: ARs are differentially expressed in GP what should be considered in prognostic models which include AR. In nodal metastases, ARs are significantly down-regulated suggesting decreased dependence on androgens already under hormone-naïve conditions. AR expression level is not prognostic in nodal positive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…However, other studies that only included lymph node metastases showed a lower or constant level of AR compared with primary prostate cancer. [24][25][26] Notably, expression of PSA, PSAP, and AR is not restricted to prostatic tissue. 5,6,27 High specificity is an essential requirement for diagnostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies that only included lymph node metastases showed a lower or constant level of AR compared with primary prostate cancer. [24][25][26] Notably, expression of PSA, PSAP, and AR is not restricted to prostatic tissue. 5,6,27 High specificity is an essential requirement for diagnostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…AR is important in male urogenital development, and is strongly expressed in the majority of prostatic adenocarcinomas [2][3][4][5][6][7][8]. Historically, AR expression was considered to be relatively specific to prostate carcinoma with expression maintained even in poorly differentiated tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cancer stem cells that possess quiescence and selfrenewal capability is consistent with selection model, so explaining the outgrowth of prostate cancer after ADT [47,50]. Anyway, the most reasonable and likely scenario is the coexistence of both models of resistance in a same tumor or patient, existing some evidence regarding this state [51,52].…”
Section: Mechanisms Of Resistance In Prostate Cancermentioning
confidence: 72%